Mitigating river basin development using landscaping measures - Salleh, Dani; Mariyappan, Raman (2010)
During the last decade public concern for environmental issues has included demands to revert the rivers back to their natural look. Major urban river management measurement had taken place during the last decade. These measures include the Water Pollution Control law, Comprehensive Flood Control Measures plan, and River Beautification Program. While, the main purpose of river improvement (beautification) is to control flood as efficiently as possible. The river beautification program has been expanded to cover the full length of the river. Under these projects preservation and improvement of river, a high priority was given in considering development proposal of large development. Increasing the public concern over the demand of utilization of public water bodies for recreational purposes requires the relevant authorities expanding the greenery and beautification measures in mitigating the urban rivers. Therefore, a systematic preservation and restoration of urban rivers by the responsible agency for river management should play main role in establishing the plan for river environment management. The direction of these measures over the years is towards the management of both flood and ordinary flow in rivers. by integrated planning and management of urban development. The discussion in this paper treating Malaysia's experience as a case study outlines development of urban water management and the efforts by respective authorities towards preparing integrated water management in the country. At the end of this paper, suggestions will be made on how the local authorities can play their roles for a friendly monitoring of land development besides stimulating development.